Salmonella Typhimurium Sensing Strategy Based on the Loop-Mediated Isothermal Amplification Using Retroreflective Janus Particle as a Nonspectroscopic Signaling Probe - Chun, Hyeong Jin; Kim, Seongok; Han, Yong Duk; Kim, Ka Ram; Kim, Jae Ho; Yoon, Hyunjin; Yoon, Hyun C. (ACS Sensors, 2018)
Loop-mediated isothermal amplification (LAMP) is a powerful gene amplification method, which has many advantages, including high specificity, sensitivity, and simple operation. However, quantitative analysis of the amplified target gene with the LAMP assay is very difficult. To overcome this limitation, we developed a novel biosensing platform for molecular diagnosis by integrating the LAMP method and retroreflective Janus particle (RJP) together. The final amplified products of the LAMP assay are dumbbell-shaped DNA structures, containing a single-stranded loop with two different sequences. Therefore, the concentration of the amplified products can be measured in a manner similar to the sandwich-type immunoassay. To carry out the sandwich-type molecular diagnostics using the LAMP product, two DNA probes, with complementary sequences to the loop-regions, were prepared and immobilized on both the sensing surface and the surface of the RJPs. When the amplified LAMP product was applied to the sensing surface, the surface-immobilized DNA probe hybridized to the loop-region of the LAMP product to form a double-stranded structure. When the DNA probe-conjugated RJPs were injected, the RJPs bound to the unreacted loop-region of the LAMP product. The number of RJPs bound to the loop-region of the LAMP product was proportional to the concentration of the amplified LAMP product, indicating that the concentration of the target gene can be quantitatively analyzed by counting the number of observed RJPs. Using the developed system, a highly sensitive and selective quantification of Salmonella was successfully performed with a detection limit of 102 CFU.
Keywords: Janus particles; Loop mediated isothermal amplifications; Molecular diagnostics; Optical bio-sensing; Salmonella typhimurium; Aluminum; Bacterial Typing Techniques; Base Sequence; Biosensing Techniques; DNA Probes; DNA, Bacterial; DNA, Complementary; Gold; Light; Limit of Detection; Manufactured Materials; Microtechnology; Nucleic Acid Amplification Techniques; Nucleic Acid Hybridization; Optical Imaging; Optical Phenomena; Salmonella typhimurium; Silicon Dioxide; Succinimides; loop-mediated isothermal amplification; molecular diagnostic; optical biosensing system; retroreflective Janus particles; Salmonella Typhimurium